2020
DOI: 10.1111/acps.13252
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive functioning after electroconvulsive therapy in late‐life depression: A 4‐year prospective study

Abstract: Objective Despite the proven efficacy and safety of ECT, there is still concern about the possible cognitive side effects of ECT in older patients. In this study, we aimed to characterize the long‐term cognitive effects of ECT in patients with late‐life depression (LLD) from before the start until 4 years after the index ECT course. Methods Fourty one patients aged 55 years and older with a unipolar depression, referred for ECT, were included. The neuropsychological test battery was assessed prior to ECT, 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Previous studies have revealed that cognitive effects of ECT are mild and transient regardless of consent status [57]. Even in older patients, long-term follow-up does not reveal significant cognitive decline [58,59]. Additionally, ECT was well tolerated even in older patients with pre-existing cognitive impairment [60].…”
Section: Cognitive Effects Of Ect In Patients Without Dmc-tmentioning
confidence: 98%
“…Previous studies have revealed that cognitive effects of ECT are mild and transient regardless of consent status [57]. Even in older patients, long-term follow-up does not reveal significant cognitive decline [58,59]. Additionally, ECT was well tolerated even in older patients with pre-existing cognitive impairment [60].…”
Section: Cognitive Effects Of Ect In Patients Without Dmc-tmentioning
confidence: 98%
“…The therapeutic effect of ECT is achieved by administering a stimulus substantially above the seizure threshold, yet as the stimulus increases, it can worsen cognitive outcomes 1 . Although most ECT-associated cognitive adverse effects are acute and transient, some effects can persist for 6 months or longer 2–4 . These adverse effects include changes in attention, verbal fluency, memory, and executive function and can lead to suboptimal outcomes and worsening stigma toward the procedure 5,6 .…”
Section: Highlightsmentioning
confidence: 99%
“…1 Although most ECTassociated cognitive adverse effects are acute and transient, some effects can persist for 6 months or longer. [2][3][4] These adverse effects include changes in attention, verbal fluency, memory, and executive function and can lead to suboptimal outcomes and worsening stigma toward the procedure. 5,6 Present day dosing algorithms, such as seizure threshold titration and formula dosing based on age and sex, lack scientific rationale as they are unable to account for individual variability to electric current (head shape, skull thickness, tissue composition, etc).…”
mentioning
confidence: 99%
“…Electroconvulsive therapy (ECT) is an established effective treatment for severe depression, especially for older adults [ 1 4 ]. Although ECT induces multiple generalized seizures by the application of electric currents through the scalp under general anesthesia, ECT is a safe treatment with a low mortality rate [ 5 ], and is not associated with long-term cognitive decline in older patients [ 6 , 7 ] nor with increased risk of developing dementia [ 8 ], although some individuals experience cognitive side-effects [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%